Foreclosure and tunneling with partial vertical ownership - Matthias Hunold; Vasilisa Petrishcheva (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2022)
We study the incentives of firms that hold partial vertical ownership to foreclose rivals. Compared to a full vertical merger, with partial ownership, a firm may obtain only part of the target's profit but may nevertheless be able to influence the target's strategy significantly. The target may be either a supplier or a customer, which opens the scope for either input foreclosure or customer foreclosure. We show that the incentives to foreclose can be higher, equal, or even lower with partial ownership than with a vertical merger, depending on how the protection of minority shareholders and transfer price regulations are specified.
Keywords: G34; L22; L40; 330; Backward ownership; Entry deterrence; Foreclosure; Minority shareholdings; Partial ownership; Uniform pricing; Vertical integration